Effect of dates of sowing and cutting for fodder on fodder yield, seed yield and oil yield of oilseed rape genotypes: Effect of dates of sowing and cutting for fodder on fodder yield, seed yield and oil yield of oilseed rape genotypes - AARADHANA CHILWAL; VIRENDER SARDANA; KULVIR SINGH (Journal of Oilseeds Research, 2020)
A field study was conducted with three genotypes , three dates of sowing and three time of cutting for fodder. Genotype OS-1 and sowing date of 10th October without any cutting for fodder resulted in highest seed, stover and oil yield. However, sowing on 25th September with OS-1 and GSC-7 genotypes produced highest fodder yield at 35 days after sowing (DAS) and 50 DAS cutting, respectively.